Two new species of penicillate millipedes (Diplopoda, Polyxenidae) from Phu Quoc Island in southern Vietnam - Huynh, Cuong; Veenstra, Anneke A (Zootaxa, 2018)
Two new penicillate millipede species from the genera Unixenus and Monographis (Diplopoda, Polyxenidae) were collected from Phu Quoc Island, Vietnam’s largest island. Unixenus intragramineus sp. n. was found within the stem of a creeping grass growing on an unstable, sandy substrate in the intertidal zone. The defining taxonomic characteristics of the genus Unixenus were apparent in U. intragramineus sp. n., but it is distinctively different from all described species. Monographis phuquocensis sp. n. belongs to a group of Monographis species which have their antennal sensilla arranged in a crescent-shape; but the structure of the labrum and telotarsus observed in this new species differs from other described Monographis.